Perilaku Masyarakat Multi Agama dalam Kehidupan Bertetangga Desa Sekaran Kec. Kayen Kidul Kab. Kediri - Jannah, Alfin Uhailul; Prastiyani, Eka Diah; Hamidah, Dewi (Prodi Sosiologi Agama, 2018)
Community diversity shows a nation that is rich in tradition and culture. Indonesia is a country of diverse ethnicity, race, and culture but we are still one called Bhineka Tunggal Ika. In the order of society, it is reflected in the form of tolerance practiced in the daily life of Sekaran Village. The multi-religious community that lives side by side makes researchers want to know their neighbors’ lives. The method used in reviewing this research is a qualitative approach, using a social fact paradigm. The results of the research are Sekaran is an exemplary village for people who have multiple religions and the practice of tolerance in neighboring life starts from the small things in the social environment. The conclusion obtained in this study is that the lives of neighboring communities of Sekaran are inseparable from the lives of the people in general, which is the difference between the people of Multi-Religion. The people’s life is very keeping the peace between religious groups which makes the village a model of religious tolerance in the Kayen Kidul Subdistrict.